Design of an Eight-Wheeled Mobile Delivery Robot and Its Climbing Simulations - Kaya, Omer Mutlu Turk; Erdemir, Gokhan (IEEE, 2023)
Delivery robots are becoming widespread all around the world recently. They are commonly used in America, Europe, and Asia. The primary purpose of these robots is the delivery service of goods such as food, parcels, groceries, etc. On the other hand, the developments bring the problems together. One of them is climbing the curbs and stairs. Six-wheeled delivery robots and most four-wheeled delivery robots have often faced problems climbing up and down these obstacles. According to some cases reflected in the press, those wheel numbers and mechanisms are not enough to easily pass over the curbs and stairs. Especially most six-wheeled robots have one bogie mechanism. The study aims to design an eight-wheeled mobile delivery robot that paves the way for curb & stair climbing. It has a double bogie mechanism; one is in front, and the other is in the back. Undoubtedly, the robot has a cargo compartment. The proposed delivery robot structure was designed in the Catia v5 3D CAD software and simulated in Gazebo 9 simulation software.
Keywords: Delivery robot; 8-wheeled robot; mobile robot; and climbing simulation; Computer Science